Hungary and Poland: The Two Antemurales in the Late Fifteenth Century - Tafiłowski, Piotr (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2023)
The aim of this article is to analyze and confront the two conceptions—Polish and Hungarian—of Antemurale Christianitatis developed in the late fifteenth century. It is based, in the first part, on the published correspondence between King Matthias Corvinus of Hungary (1458–90) and Pope Sixtus IV (1471–84). These documents are interesting because they allow us to follow the duplicity of the policies practised by Matthias. Taking advantage of his involvement in the struggle against the Turks, the Hungarian king sought to attain other goals. The second part of the article is based on the political works of an Italian humanist living in Poland, Philippus Buonaccorsi, called Callimachus. I compare the attitudes of two then-hostile kingdoms, which earlier (in the time of Władysław Warneńczyk, d. 1444) and later (in the time of Władysław Jagiellończyk, d. 1516, and his son Ludwik, d. 1526) were connected by personal union and dynastic ties, respectively, towards the problem of Antemurale.